Estimation of the Wenchuan Earthquake Rupture Sequence Utilizing Teleseismic Records and Coseismic Displacements - Deyu Yin; Qifang Liu; Jingke Wu (Advances in Civil Engineering)
For the 12 May 2008 Mw 7.9 Wenchuan earthquake, two imbricate faults, Beichuan fault and Pengguan fault, have ruptured simultaneously. Special attention should be paid to the point of 40 km northeast of the epicenter, in which the Xiaoyudong fault intersects the above two faults, creating a complex fault structure. Surface rupture data from field surveys and previous research of dynamics studies indicate that an important transformation may take place at the intersection. But, few studies about inversion of source rupture process have focused on this issue. We establish a multiple-segment, variable-slip, finite-fault model to reproduce the rupture process and distinguish rupture sequence. Based on the nonnegative least square method and multiple-time-window approach, the spatial and temporal distribution of slip for three rupture sequences are exhibited, using teleseismic records and coseismic displacements. The conformity between synthetic and observed teleseismic records as well as the slip value of the shallowest subfaults and the coseismic displacements is utilized to calibrate the model. The results are as follows: (1) The teleseismic records inversion alone could not distinguish different rupture sequences. However, in order to make the slip of the Hongkou and Yingxiu area coincide with the field investigation, only the Beichuan fault has a bilateral rupture on the point of intersection of Xiaoyudong fault. So the possible rupture sequence is that the earthquake started at the low dip angle part of southern Beichuan fault, and then it propagated to the Pengguan fault, which caused the rupture of Xiaoyudong fault. Then the southern part of Beichuan fault with high dip angle is triggered by the Xiaoyudong fault. (2) The coseismic displacements constraint can control the slip of subfaults near the surface and has little impact on the deeper subfaults. (3) The maximum slip on the fault is located near the Yingxiu and Beichuan area; moreover, the slip is mainly distributed at the shallow region rather than at the deep, which led to serious disasters. Meanwhile, majority of the aftershocks occur in the periphery of large slip.